Long Term Effect of Post-Covid-19 Syndrome on Hematological Parameters in Iraqi People - Sara Basim Zwain; Sami Raheem Al-Katib; Falah Mahdi Dananah; Basim MH Zwain (مجلة الكوفة الطبية)
Background: The COVID-19 epidemic, which is still ongoing, has a significant effect on health care both in Iraq and worldwide. Further strain on health systems was caused by successive waves of altered viruses, further enhancing virus dissemination.  Persistent symptoms may last for several months following the initial COVID-19 infection. The illness is called post-acute sequelae of SARS-CoV-2 infection, or Long COVID (PASC). Long-term COVID-19 infection can affect various organs and systems, including the hematological system, and cause many symptoms. Hematological problems have been observed in several investigations with COVID-19 individuals. Poor outcomes and an increased risk of severe disease are linked to the majority of these changes.